Ileosigmoid knot: A case report of the lethal twist - Basma Dghoughi, MD; Basma Beqqali, MD; Kaoutar Maslouhi, MD; Hamza Hamdani, MD; Omar Sbiyaa, MD; Sara Benammi, MD; Hamid Mohammadine, PhD; Abdellatif Settaf, PhD; Zaynab Iraqi Houssaini, PhD; Ola Messaoud, PhD; Laila Jroundi, PhD; Omar El Aoufir, PhD (Radiology Case Reports)
Ileosigmoid knot (ISK) is a rare and rapidly fatal surgical emergency characterized by the twisting of the ileum around the sigmoid colon, leading to acute bowel obstruction, ischemia, and gangrene. Due to its nonspecific clinical presentation, ISK is often misdiagnosed causing a delay of definitive treatment. The condition is most frequently reported in regions with high-fiber diets and anatomical predispositions, but remains a globally uncommon entity. Radiological imaging, particularly CT scans, plays a crucial role in preoperative diagnosis, with the whirl sign including sigmoid and ileum being a key diagnostic clue. However, most cases are only confirmed intraoperatively, and outcomes depend on the extent of bowel necrosis and the timeliness of surgical intervention. Mortality rates remain high, particularly in cases complicated by sepsis and multiorgan failure. We present the case of a 49-year-old male who developed acute abdominal pain, with CT imaging and laparotomy confirming an ileosigmoid knot, ultimately resulting in a fatal outcome.